Pinpointing Neural Correlates of Attachment in Poly-Drug Use: A Diffusion Tensor Imaging Study - Fuchshuber, J.; Unterrainer, H. F.; Hiebler-Ragger, M.; Koschutnig, K.; Papousek, I.; Weiss, E. M.; Fink, A. (Frontiers in Neuroscience, 2020)
An increasing amount of evidence indicates the significance of attachment in the etiology of poly-drug use disorder (PUD). The aim of this study was to investigate associations between PUD and adult attachment in particular, with a focus on white matter fiber tract integrity. For this purpose, we selected several regions-of-interest based on previous findings which were examined for their role in PUD and estimated whole-brain associations between adult attachment and white matter integrity. A total sample of 144 right-handed males were investigated (Age: M = 27; SD = 4.66). This included a group of patients diagnosed with PUD (n = 70) and a group of healthy controls (HC; n = 74). The Adult Attachment Scales (AAS) was applied to assess attachment attitudes in participants. Diffusion Tensor Imaging was used to investigate differences in white matter integrity. The findings suggest substantially less attachment security in PUD patients compared to HC. Furthermore, PUD patients exhibited reduced integrity in white matter fiber tracts, most pronounced in the bilateral corticospinal tract, the fronto-occipital fasciculus and the right inferior longitudinal fasciculus. However, these results were not controlled for comorbid depressiveness. With regard to associations between adult attachment and white matter integrity, the results for PUD patients indicate a negative relationship between “Comfort with Closeness” and the structural integrity of a cluster comprising parts of the right anterior thalamic radiation, the inferior fronto-occipital fasciculus and the uncinate fasciculus. Despite being limited by the cross-sectional design of this study, the results emphasize the significance of attachment in PUD etiology, both at a behavioral and a neurological level. Largely in line with previous research, the findings revealed tentative links between adult attachment and white matter fiber tracts related to cognitive and affective functions in PUD patients.